TEKNOLOGI PENYEDIAAN AIR MINUM UNTUK KEADAAN TANGGAP DARURAT - Herlambang, Arie (Center for Environmental Technology, 2010)
In the event of natural disasters such as earthquakes, tsunamis, landslides, floods and droughts, water occupies a key role in disaster relief. The presence of water is important for drinking, cooking and support the refugee areas of environmental sanitation and avoiding disaster victims of diseases waterborn disease. Water problem in disaster conditions may occur partly as a result: the disturbance of water sources because change of water quality, to become turbid or salty, the destruction of a piping system, treatment plant damage, disruption of distribution systems, or the scarcity of water in evacuation areas. Introduction of water quality becomes important to determine which process technology will be used and saved investments in emergency conditions. Priority handling of clean water usually comes first in the refugee areas with communal system, because the need of water for bathing, washing and toilet is big enough, while for a drink in the early events during disaster dominated by bottled water, but for their long-term, they have to boil water. For remote areas and difficult to reach individuals who usually use Ã‚Â system more simple and easily operated. Water Supply Technology for emergency response has the characteristic 1). Able to operate with all sorts of water conditions (flexible & adaptable), 2). Can be operated easily, 3). Does not require much maintenance, 4). Little use of chemicals, and 5). Portable and easy removable (Mobile System).Ã‚Â Keywords : Ã‚Â Water Quality, Water Treatment Technology, Drinking Water, Emergency Response, filtration, ceramic filtration, Ultra filtration, Reverse Osmosis, Ultraviolet Sterilizer, Ozonizer, Disinfection.